Performance Evaluation of Software Defined Network (SDN) Based Surveillance System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There are several challenges in traditional video surveillance systems such as storagesize and power consumption. In this study, the software-defined network is used to findsolutions to these issues. SDN is a new technology that simplifies the control of the network bydata plane is separated from the control plane. Also, it enables the multi-camera networks invideo monitoring systems to be reconfigured dynamically. The main idea of the proposed systemis to find a way for activate the cameras recording when necessary only by taking advantage ofthe characteristics of SDN and without using motion detection sensors. As far as we know, weare the first to take advantage of SDN features to implement activity and sleep modes on cameraswithout the need for sensors. A use case is installing cameras on a roadside to monitor vehiclemovement on the campus. We created an application that interacts with the controller throughRESTful API web services. The application sends the time of active mode and the time of sleepmode for each camera to the controller. Also, the controller developed to activate the cameras orreturn them to standby mode according to the specified time by the network application. Finally,videos sent from the cameras are merged into a single video on the server, which reduces thetime and effort spent when analysing received video streams. The system was simulated usingthe Mininet emulator and the POX controller. The results showed that the proposed systemovercomes the traditional system in terms of reducing power consumption and storage size, thusreducing the cost of multi-camera systems.